EVALUASI IMPLEMENTASI STRATEGI ANTI-FRAUD (STUDI PADA PT BANK BUKOPIN TBK.) - Laksmidewi, Laras (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research is to discover anti-fraud strategy executed by PT Bank Bukopin Tbk. in order to prevent, detect, investigate, and reporting fraud using the qualitative method. The proceeding data were obtained through interview technique and equipped with secondary data accessed from various sources. The result of this research shows that strategies conducted by Bank Bukopin have fulfilled the four main pillars of anti-fraud strategy as stated in Surat Bank Indonesia No. 13/ 28 /DPNP. An indication which shows Bank Bukopin has executed their anti-fraud very well can be seen through its succeed on the following strategies such as quarterly campaign, material presented during induction, direct socialization with SKAI, Fraud Risk Assessment, Surprise Audit, and Whistleblowing System. Keywords: Fraud, Anti-fraud Strategy, Banking Industry.